Analysis of Judges' Decisions in Gender-Based Violence Cases at the Religious Courts - Dimyati, Yayat (STAI Miftahul Ula Nganjuk, 2024)
Gender-based violence (GBV) remains a serious challenge in Indonesian society, including within the family. Religious Courts, as legal institutions that handle family disputes, have an important role in providing justice to victims, especially women. This article analyses the pattern of judges' decisions in cases of gender-based violence in the Religious Courts with a focus on the factors that influence decisions and the relevance of these decisions to the principles of gender justice. Using normative and empirical juridical approaches, it is found that despite efforts to protect victims of GBV, there are still challenges in proof and application of substantive justice principles. This article recommends training for judges, improving access to legal aid for victims, and improving regulations to strengthen legal protection for victims of gender-based violence.